EFL STUDENTS’ EXPERIENCES OF WILLINGNESS TO COMMUNICATE IN EXTRAMURAL DIGITAL CONTEXT - Halyasmina Amira; Kusrin Kusrin; Yousef Bani Ahmad (Universitas Muhammadiyah Makassar, 2021)
This study investigate the positive relationship between extramural digital activities and EFL students’ willingness to communicate. Extramural digital context is learning English outside the classroom without teachers’ involvement. It encourages EFL students to feel more comfortable in L2 willingness to communicate. Furthermore, this research investigated students’ experiences and factors that may influence EFL students’ willingness to communicate towards extramural digital context using qualitative research, specifically case study as the research design. The researcher collected the data from six EFL students from several universities in Indonesia with four female and two male using semi-structured interview and questionnaires. The interviews data were analyzed by using thematic analysis and using descriptive statistics analysis for the questionnaires. The findings showed that the convenience of extramural digital context and students’ self-confidence indicate as the factors that influence students’ willingness to communicate using English. Additionally, based on students’ experiences of using extramural digital context, listening to music is considered as the most frequently used by students. This research contribute to gain deep understanding about L2 willingness to communicate and extramural digital context. In pedagogical insight, this research help English teacher to facilitate EFL students in extramural digital context to increase students’ willingness to communicate.